(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Relevance. The use of triticale, which combines the high productivity potential of wheat with the enhanced adaptive properties of rye, is an effective way to meet the needs of the population for organic food and livestock for high-quality feed. Triticale is a crop that can be grown in different soil and climatic zones and has a multifunctional use, which has taken its place in the structure of crop production. The potential yield of the best triticale varieties exceeds 10 tonnes per hectare. However, despite this, triticale still does not occupy a proper place in the structure of grain crops in Ukraine. The increase in the area under triticale crops in Ukraine will help expand opportunities for using the grain for food, technical and fodder purposes. The aim of the work is to assess the current state of winter triticale cultivation, to analyse the data from the literature on technological measures to increase grain yields of the crop. Methods. The methodological tools of the work included: comparative analysis, dialectical method, economic and statistical method, synthesis, theoretical generalization, analytical and expert evaluation method. Based on the results of the analysis of domestic and foreign scientific publications, as well as the processing of Internet resource data, the data obtained on the cultivation of winter triticale were formed, the main technological factors influencing its productivity were analyzed and outlined. Research results. Winter triticale is an intensive crop with a fairly high resource intensity of technology, which, under conditions of sufficient moisture and nutrient supply, forms a high level of yield. A prerequisite for ensuring stable yields of triticale grain is the application of mineral fertilizers, with the levels of their application depending on the type of soil and its fertility. The main attention should be paid to optimizing nitrogen nutrition, as this crop is more biologically active in the accumulation of protein in the grain compared to other cereals. Triticale responds positively to high fertilizer rates. Conclusions. The use of mineral fertilizers in scientifically recommended doses in modern agrotechnologies of triticale cultivation is an integral part and is environmentally safe for the environment and human health. Foliar fertilization is an effective way to ensure balanced plant nutrition and eliminate the deficiency of certain trace elements.